Neuroendocrine Control of Growth Hormone Secretion - Muller, Eugenio E; Locatelli, Vittorio; Cocchi, Daniela (Physiological reviews, 1999)
Department of Pharmacology, Chemotherapy, and Toxicology, University of Milan, Milan; and Department of Biomedical and Biotechnology Sciences, University of Brescia, Brescia, Italy Müller, Eugenio E., Vittorio Locatelli, and Daniela Cocchi. The secretion of growth hormone (GH) is regulated through a complex neuroendocrine control system, especially by the functional interplay of two hypothalamic hypophysiotropic hormones, GH-releasing hormone (GHRH) and somatostatin (SS), exerting stimulatory and inhibitory influences, respectively, on the somatotrope. The two hypothalamic neurohormones are subject to modulation by a host of neurotransmitters, especially the noradrenergic and cholinergic ones and other hypothalamic neuropeptides, and are the final mediators of metabolic, endocrine, neural, and immune influences for the secretion of GH. Since the identification of the GHRH peptide, recombinant DNA procedures have been used to characterize the corresponding cDNA and to clone GHRH receptor isoforms in rodent and human pituitaries. Parallel to research into the effects of SS and its analogs on endocrine and exocrine secretions, investigations into their mechanism of action have led to the discovery of five separate SS receptor genes encoding a family of G protein-coupled SS receptors, which are widely expressed in the pituitary, brain, and the periphery, and to the synthesis of analogs with subtype specificity. Better understanding of the function of GHRH, SS, and their receptors and, hence, of neural regulation of GH secretion in health and disease has been achieved with the discovery of a new class of fairly specific, orally active, small peptides and their congeners, the GH-releasing peptides, acting on specific, ubiquitous seven-transmembrane domain receptors, whose natural ligands are not yet known.